2015
DOI: 10.1016/j.jcf.2015.04.006
|View full text |Cite
|
Sign up to set email alerts
|

Vaccine coverage in CF children: A French multicenter study

Abstract: This study shows a defect in vaccine coverage for both routine immunization and vaccines more specifically recommended in CF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 26 publications
1
14
0
Order By: Relevance
“…Severe acute deterioration in lung function and increased morbidity and mortality have been reported in CF patients with influenza . This underlines the need to get immunised in every influenza season . We found that approximately one in every three subjects with CF was immunised with PPSV23 and one in every 10 subjects did so at the appropriate age.…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…Severe acute deterioration in lung function and increased morbidity and mortality have been reported in CF patients with influenza . This underlines the need to get immunised in every influenza season . We found that approximately one in every three subjects with CF was immunised with PPSV23 and one in every 10 subjects did so at the appropriate age.…”
Section: Discussionmentioning
confidence: 53%
“…In this study from France, Masson et al. found insufficient coverage rates for DTP‐IPV‐Hib, PCV, BCG, MMR and HBV. Vaccination coverage for vaccines specifically recommended for CF children in France (PPSV23, VZV and HAV) was considerably low .…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…We examined BMI as a categorical measure, and for those 21 years of age and older, categorized as underweight (<18.5), normal (18.5-24.9), overweight (25-29.9) and obese (>30.0). Those 2 years of age to 20 years of age were categorized in the previously described categories using the CDC-Growth Age BMI charts [12]. The chart uses percentiles, and considers both gender and age.…”
Section: Categorization Of Body Mass Index Valuesmentioning
confidence: 99%
“…The chart uses percentiles, and considers both gender and age. Underweight is defined as less than the 5th percentile, normal as between the 5th and 85th percentile, overweight defined as between the 85th and 95th percentile and lastly, obese as at or above the 95th percentile [12,13].…”
Section: Categorization Of Body Mass Index Valuesmentioning
confidence: 99%